Cannabinoids as anticancer and neuroprotective drugs: Structural insights and pharmacological interactions—A review. (December 2021) - Pugazhendhi, Arivalagan; Suganthy, Natarajan; Chau, Tan Phat; Sharma, Ashutosh; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Karuppusamy, Indira; Brindhadevi, Kathirvel
Graphical abstract: Highlights: Cannabinoids (CB) exhibit anticancer effect via antiproliferation, autophagy and apoptosis. CB inhibit carcinogenesis blocking invasion, angiogenesis and metastasis. Nanoformulated CB enhances drug delivery, bioavailability, biocompatibility. Antioxidant, antiglutamatergic, antiinflammatory effect of CB protect neuronal cells. Abstract: Cannabinoids are the major chemical constituents of the plant Cannabis sativa L. and are known to exhibit a wide range of pharmacological effects viz ., psychotropic, analgesic, anticancer, antiinflammatory, antidiabetic, anticonvulsive, antibacterial and antifungal etc. The use of cannabis, cannabinoids and their products is restricted in several countries due to the high risk of misuse. Recently, cannabinoids have regained the interest of the researchers due to their therapeutic applications. Ever since the discovery of the cannabinoids, most of the studies carried out on the evaluation of their biological activities were limited to only preclinical levels. The quality of the preclinical data still remains only low to moderate, thus, leaving behind an uncertainty in their use for therapeutic applications. Problems associated with the solubility, stability and bioavailability of the cannabinoid drugs are also a major concern in the quality of the study. Nanoparticle based drug delivery system could be a potential method to increase the reliability of the data. While considering the immense pharmacological properties of the cannabinoids, there is an urgency to perform intensive clinical trials and to know their mechanism of action in various disease conditions, evaluate their efficacy and safety, and register them as drug candidates. This review highlights the chemistry, types and biological activities of the cannabinoids such as THC, CBD and CBN in focus with their anticancer activity, neuroprotective effect and nanoformulating the cannabinoid drugs.